Effectiveness of whistleblower laws in combating corruption - Rajeev K. Goel; Michael A. Nelson (Bank of Finland, Institute for Economies in Transition (BOFIT), 2013)
Whistleblower laws are becoming important governance tools in both the public and private sectors. To examine the effectiveness of whistleblower laws and their awareness, this study creates a unique internet-based measure of awareness about whistleblower laws and provisions, focusing on the United States. Placing the analysis within the larger corruption literature, our results show that greater whistleblower awareness results in more observed corruption and this holds across specifications. Internet awareness of whistleblower laws appears to be more effective at exposing corruption than the quantity and quality of whistleblower laws themselves.
URN:NBN:fi:bof-201408072009
Keywords: K4; H7; 330; corruption; whistleblowers; law enforcement; internet; United States